Chapter Advanced Space Flight Mechanical Qualification Test of a 3D- Printed Satellite Structure Produced in Polyetherimide ULTEMTM - Martín-Moreno, Almudena (InTechOpen, 2018)
The aim of this work is to demonstrate the use of additive manufacturing with thermoplastic material in the whole functional structure of spacecraft and to mechanically qualify it for space flight. For such purpose, an 8 U CubeSat structure was manufactured in polyetherimide (PEI) ULTEM™ through 3D printing and passed several vibration tests. The results are compared with those obtained in the qualification of the same structure manufactured in aluminum alloy AA-6082 T651 through a conventional CNC method. The qualification consisted of passing the vibration requirements in quasi-static, sine, and random tests to fly in PSLV launcher. Finally, a robustness test for the 3D-printed structure is included, and all the results are analyzed. This study is being part of the H2020 European Project ReDSHIFT (Project ID 687500).